The numismatics on antiquity as a developing element of historical consciousness (Research, Society and Development, 2020)
In studying the theories of historical consciousness development, it can be verified that this concept can be found along the course of human history, being more than only fruit of modern thought. Historical consciousness is the hability of someone to see himself as an agent of history, influenced by it as well as someone who can influence it, being aware of historical processes - this means that the elements of the past influence the current complexity of our society. From the theories of historical consciousness, this paper aimed to analyze not only its development among the peoples of antiquity, especially in ancient Rome, but also in the development of this consciousness today. The methodology used was an analysis based on the works of Hans-Georg Gadamer (1900-2002), Philippe Ariès (1914-1984), Jörn Rüsen (1938-) and Agnes Heller (1929-2019). We observe how numismatics served as a contribution to the development of such consciousness in antiquity and, as well, its study helps the history discipline achieve the objectives established by public education policies, forming conscious young people with critical sense and analytical capacity.